Model Pengajaran Bahasa Arab Berbasis Nilai Moderasi Islam di Pesantren - Ishaqiyah, Arinil; Ayu Nuriyana, Siti; Makinuddin, Muhammad (Minhaj Pustaka, 2025)
Through descriptive research with direct data collection from learning activities at the Mabaus Sholihin Islamic Boarding School, it was found that the Arabic language teaching model that integrates Islamic moderation values ​​is able to improve linguistic competence while shaping the moderate character of students. Students are not only proficient in reading and understanding Arabic texts, but are also able to internalize the values ​​of rahmatan lil 'alamin in everyday life. This model maintains Islamic boarding school traditions such as sorogan and bandongan, but is enriched with communicative methods, interactive discussions, and project-based learning so that it is more relevant to the needs of the times. The results of the study confirm that the integration of Islamic moderation values ​​in Arabic language teaching at the Mabaus Sholihin Islamic Boarding School is an effective strategy for producing a generation of Muslims who are not only experts in religious knowledge, but also have a tolerant, balanced, and progressive attitude in facing the challenges of a multicultural society.